Vertical Transmission of Bacterial Eye Infections, Angola, 2011–2012 - Mar Justel; Isabel Alexandre; Prudencio Martínez; Iván Sanz; Ana Rodriguez-Fernandez; Itziar Fernandez; Jose Carlos Pastor; Raúl Ortiz de Lejarazu (Emerging Infectious Diseases, 2015)
To determine transmission rates for neonatal conjunctivitis causative microorganisms in Angola, we analyzed 312 endocervical and 255 conjunctival samples from mothers and newborns, respectively, during 2011–2012. Transmission rates were 50% for Chlamydia trachomatis and Neisseria gonorrhoeae and 10.5% for Mycoplasma genitalium. Possible pathogenic effects of M. genitalium in children’s eyes are unknown.